Metode Biaya Rata-Rata Bergerak Perpetual dalam Program Aplikasi Persediaan Barang Dagang - Nazel Kasyfia Mumtaza; Heldalina Heldalina; Muhammad Syahid Pebriadi (Jurnal Tekno Kompak, 2023)
Abstract−The purpose of this study is to determine the correct calculation of the cost of inventory, as well as to produce an application program for merchandise inventory using the perpetual moving average method using PHP at Ocean Fishing Store. This research is in the form of a case study at the Ocean Fishing Store using a sample of sales and purchase transaction data in March-May 2022. This application program was created using PHP as the front-end and MySQL server as the back-end. From this study it was found that the Ocean Fishing Store does not determine the cost of inventory for merchandise and does not record merchandise inventory so that it is difficult to know the remaining inventory of merchandise. Therefore, with the application program created in this study, it is hoped that it can help Ocean Fishing Store in making merchandise inventory cards to make it easier to find out stock.Keywords: Goods Inventory, Moving Average Cost Method, Goods Inventory Card